The Effect of Using Smartphones on the Mathematics Learning Outcomes of Class X Students at SMA Negeri 2 Tondano - James U. L. Mangobi; Derel F. Kaunang; Varlina Fani Rantung (Departement of Mathematics Education, 2023)
This study investigates the impact of smartphone use on mathematics learning outcomes for SMA Negeri 2 Tondano students in grade ten. This investigation employs a survey methodology. This investigation was conducted at SMA Negeri 2 Tondano during the even semester of the academic year 2022/2023. This study's population consisted of all pupils in class X, which consisted of two classes and 58 students; questionnaires and documentation were used to collect data. The questionnaire provides information regarding Smartphone Use. In contrast, the documentation exposes the mathematics learning outcomes of grade X students from SMA Negeri 2 Tondano during the even semester of the academic year 2022/2023. Simple Linear Regression Analysis will be utilized to test the hypothesis in this investigation. Using the regression equation Y = 40.443 + 0.517X, with Fcount = 15.076 > Ftable = 4.10 and Sig value. = 0.000 alpha = 0.05; and the correlation coefficient value of 0.533, it was determined that there was a positive effect of Smartphone use on the1mathematics Learning1Outcomes of Class X1Students at SMA Negeri 2 Tondano. Thus, it can be concluded that smartphone use has a 28.4% impact1on the mathematics learning1outcomes of pupils in class X at SMAaNegeri 2 Tondano.